2021
DOI: 10.1155/2021/8294267
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Influencing Factors of Repair Effect after Peripheral Nerve Injury

Abstract: In order to improve the repair effect after peripheral nerve injury, this paper analyzes the related influencing factors. The regeneration of peripheral nerve includes two continuous and overlapping processes: the acute wound healing period and the axon seeking target tissue period. The complete and effective process of peripheral nerve regeneration includes the sprouting, growth and extension of regenerated axons, and the reconstruction of synaptic connections (neuromuscular junctions) with target organs to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Анализ топографической анатомии нервных стволов позволил выделить зоны с «суставным» типом сближения концов нерва, когда положение конечности играет существенную роль в этом сближении, и «диафизарные», когда данный аспект существенного значения не имеет [2]. При проведении топографо-анатомического исследования мы установили, что в зонах с «суставным» типом сближения концов поврежденного нерва имеются следующие особенности кровотока нервов: наличие выраженной брыжейки нервных стволов; длина сосудистой ножки кровоснабжающих нерв сосудов позволяет выполнять полный объем поступательных движений нерва; кровообращение нерва в «суставных» зонах из-за на-личия значительной степени подвижности имеет II-III тип [2,3].…”
Section: топографические особенности нервовunclassified
“…Анализ топографической анатомии нервных стволов позволил выделить зоны с «суставным» типом сближения концов нерва, когда положение конечности играет существенную роль в этом сближении, и «диафизарные», когда данный аспект существенного значения не имеет [2]. При проведении топографо-анатомического исследования мы установили, что в зонах с «суставным» типом сближения концов поврежденного нерва имеются следующие особенности кровотока нервов: наличие выраженной брыжейки нервных стволов; длина сосудистой ножки кровоснабжающих нерв сосудов позволяет выполнять полный объем поступательных движений нерва; кровообращение нерва в «суставных» зонах из-за на-личия значительной степени подвижности имеет II-III тип [2,3].…”
Section: топографические особенности нервовunclassified
“…However, further improvement of the repair effect is required, especially for large segmental peripheral nerve defects. The interrupted connection between the injured proximal and distal nerve fibers makes the repair more difficult in clinical treatment ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Analysis of Influencing Factors of Repair Effect after Peripheral Nerve Injury” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled "Analysis of Influencing Factors of Repair Effect after Peripheral Nerve Injury" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%